Borders of Music: The Horizon and the Other in Musical Experience - Ares Yebra , Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2020)
The sound recording and reproduction systems and the development without precedents of communication technologies consitute decisive elements for thinking music nowadays. In this context, the present article brings into dialogue two questions. In the first place, the question of the essence of music from the conquest of ubiquity with the appearance of Internet. Secondly, the question about the other in musical experience, addressing the concert as a communicative situation.